High, giant gastric ulcer on the back of the stomach exteriorized in the retrocavity - Asiner, Boris; Balboa, Oscar (Cirugía del Uruguay, 1973)
Two aspects of gastrectomy due to "gigantic", high. posterior gastric ulcus, exteriorized in retrocavity, are brought up for consideration. The first refers to surgical tactics in gastric abscission and its management; the second to the use of temporary transgastric intubation of efferent loop ( utilizing plastic tube) for postoperatory control and eventual solution of possible complications. The latter might consist of suture failures, llakege, etc. It is easy to perform, simple, well-tollerated and has practically no morbility.